Supplementary Table S3 from Type 2 Diabetes Mellitus and Efficacy Outcomes from Immune Checkpoint Blockade in Patients with Cancer - Cortellini,A; D'Alessio,A; Cleary,S; Buti,S; Bersanelli,M; Bordi,P; Tonini,G; Vincenzi,B; Tucci,M; Russo,A; Pantano,F; Russano,M; et al. (2023)
Summary of baseline characteristics’ distribution after the propensity score matching procedure between patients on diabetes medications and those who were not receiving diabetes medications (ratio 1:2, caliper 0.1).